Comprehensive regional study of ESBL Escherichia coli: genomic insights into antimicrobial resistance and inter-source dissemination of ESBL genes - Di Marcantonio, Lisa; Chiatamone Ranieri, Sofia; Toro, Michela; Marchegiano, Alice; Cito, Francesca; Sulli, Nadia; Del Matto, Ilaria; Di Lollo, Valeria; Alessiani, Alessandra; Foschi, Giovanni; Platone, Ilenia; Paoletti, Massimiliano; et al. (Frontiers in Microbiology, 2025)
IntroductionThe global dissemination of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) poses a significant public health challenge, particularly in regions with high antimicrobial resistance (AMR) occurrence. This study investigated the occurrence, genomic characteristics, and dissemination dynamics of ESBL-producing E. coli in Abruzzo, Italy, by analyzing 956 isolates from humans, livestock, wildlife, and food products.MethodsPhenotypic and genomic analyses were performed on the isolates to assess ESBL-E. coli occurrence and characteristics. Multilocus sequence typing (MLST) was used to identify sequence types (STs), and plasmid profiling alongside synteny analysis was conducted to investigate horizontal gene transfer and resistance gene integration. Spatial analysis was also carried out to identify hotspots of ESBL-positive isolates.ResultsAn overall ESBL-E. coli occurrence of 14.1% (135/956 samples) was found, with significant variation across hosts: companion animals exhibited the highest occurrence (16.2%), followed by livestock and food matrices (14.6%), and wildlife (7.0%). Spatial analysis identified a hotspot in northeastern Abruzzo, where ESBL-positive isolates were 5.34 times more likely to occur (p < 0.001). MLST identified 58 sequence types (STs), with ST131 dominating human isolates (12/19). In cattle, predominant sequence types were ST16565 (5 isolates) and ST540 (4 isolates); in poultry, ST43 (5 isolates), ST10 (4 isolates), and ST6215 (3 isolates) were most common; ST206 (8 isolates) was predominant in swine; and in dogs, ST10 (4 isolates) and ST3580 (3 isolates) were most prevalent. Genomic analysis revealed host-specific distributions of ESBL genes: blaCTX-M-15 predominated in humans and dogs, while blaCTX-M-1 was most common in pigs. Plasmid profiling revealed IncF and IncI plasmids as key vectors for horizontal gene transfer. Synteny analysis showed identical flanking regions of blaCTX-M-1 and blaCTX-M-15 across phylogenetically distant strains, suggesting chromosomal integration and stable maintenance of resistance genes.DiscussionThese findings underscore the interconnectedness of human, animal, and environmental reservoirs in AMR dissemination. The high genetic diversity observed within farms and the detection of shared clusters across hosts emphasize the need for integrated One Health interventions, including reduced antibiotic use in livestock and enhanced surveillance of high-risk environments. This study provides critical insights into local AMR dynamics, offering a model for regional mitigation strategies.